A constituição da identidade em crianças vítimas de abuso sexual - Minchoni, Tatiana (2010)
Subject s identity is constituted in the relation with the other, which is characterized by dialeticity, and is configured as an identification and/or recognize movement, and strangeness and/or distance. In social interactions, people with whom subject relates himself assign meanings to him and, from these, the subject will ressignify, producing sense about himself. In other words, is through these interactions that subjects organizes themselves, recognize what is yours, and acquire the sense about themselves. It can be highlighted, too, the social-historic context s importance in the self-constitution process, whereas, from this, the subject produces particular forms of perception about reality charged with cultural meaning. Thus, the self-conception, the manners of thinking, of being, of relates, of take position against experiences, coming from values internalization, roles and related, are permeated by the manner witch the others relates themselves with the subject. However, when the relation with the other happens to be in a violent way, like in children sexual abuse, there are implications in the subjects constitution, whereas violates his physical and psychological integrities, as well as the rights of dignity, respect and even healthy physical, psychological and sexual developments. Therefore, this work aims to investigate how the identity process is constituted in children victims of sexual abuse. As specific aims the research proposes: 1) to characterize the relations between child and abuser, before and after the abuse act; 2) to identify images that the subjects, abuse victims, have about themselves and; 3) to identify the features of subject s relation with their own body. Toward this aims, procedures involving drawings, painting, collage, photography, activities with cardboard, colored pens, glue and tissue snips. The research took place at the Social Assistance Specialized Reference Center, where there is the treatment of children who suffered of rights violation, which includes sexual abuse. The research subjects were 3 girl children, between 6 and 10 years old, victims of sexual abuse. The corpus analyses was done through Thematic Content Analysis, structured in three meaning nucleus: 1) self-reference without the explicit attendance of other s discourse; 2) self-reference with the explicit attendance of other s discourse; 3) The other abuser. The analysis indicates that children, research subjects, have deteriorated images about themselves, about their bodies, which is consistent with the studies in the children and adolescents sexual violence field. In the other hand, were identified, too, self-references with positive values in the cases with mention about their way-of-being, which can be read as important to subject s development. About the other s discourse towards the subjects, were identified positive observations and found that these can contribute to subject s self-image reorganization. The contribution of negative comments, on the other hand, was showed in a more clear and incisive form in subject s constitution. There is, yet, an overvaluation of the other s discourse, so the meanings attributed toward them by the other are internalized, overshadowing the self-appreciation. To conclude, it can be highlighted that the need of psychological accompaniment of the children victims of sexual abuse, based on the possibility of this trauma experience elaboration, trying to overcome, as well as can be expected that this research s results contributes to the practices of professionals who work with subjects who have their rights violated